Former BETD graduate's understanding and implementation of reflective practice in the Rundu region of Namibia - Mwala, Maria Elizabeth (Rhodes University, Faculty of Education, Department of Education, 2007)
The research, investigating how a selected group of former BETD graduates understand and implement the theory of reflective practice, is a qualitative case study carried out in the Kavango region of Namibia. The study was shaped by one of the major policy emphases in Namibia's post independence teacher education reform process - that of developing reflective teachers who actively participate in curriculum planning and take educational decisions based on their own judgment. A basic assumption underlying the study is that effective educational practice is dependent on practitioners thinking about what they are doing and acting on their reflections to improve practice. The study found that a fundamental problem preventing these teachers from implementing reflective practice in accordance with the Namibian educational reform process, is that the participating teachers neither understand the exact meaning of reflective practice nor do they have a common or shared view of the concept, in spite of their common qualifications. A key contributing factor to their problems with implementing reflective practice is the lack of a deep understanding of the reform epistemology and pedagogy revealed by the three former BETD graduates selected for the research. These are the teachers referred to in the first paragraph: The first teacher is Helena, a teacher at Duduva primary school, the second teacher is Kalishe, also teaching at the same school as Helena and the third teacher is Darius at Ntja Junior secondary school. The qualitative approach employed for the study served to illuminate and highlight specific issues related to the implementation of reflective practice that will be of considerable value for the researcher in her capacity as a teacher educator. These included among others: "¢ The teacher's need for an understanding of the key principles on which reflection is based and how to translate these into practice. "¢ The need for teachers to have a clear understanding of the role that learners play in the reflective process. "¢ The need to revisit the Basic Education Teacher Diploma (BETD) education programme, because for teachers to reflect they need a sound subject knowledge on which to base their judgments. These aspects, as well as the identification of the factors in the school system that contribute to the failure of reflective practice, provide a foundation for finding real solutions to the problems identified.
Keywords: Education -- Namibia; Teachers -- Training of -- Namibia; Educational change -- Namibia; Teacher educators -- Namibia